Ultrasound-guided cryoablation of breast fibroadenoma: a pilot trial - Golatta, Michael; Harcos, Aba (Gynecologic Oncology, 2015)
Purpose The aim of the study was to evaluate cryoablation (CA) under ultrasound guidance in the office setting with liquid nitrogen system for patients with fibroadenoma (FA).MethodsFor this prospective multicenter trial, an office-based cryosurgical system was used to treat histological confirmed benign FA with a maximum dimension of 3 cm. Sixty CA procedures were performed under ultrasound guidance. A freeze-thaw-freeze treatment cycle was performed according to the size of the FA. During the CA procedure continuous ultrasound monitoring was performed, verifying engulfment of the FA. Patients attended four follow-up visits at 1 week, 3, 6 months and 1 year and underwent ultrasound, physical examination and photography.ResultsData were collected and analyzed in 60 cases. 59 of 60 FA (98 %) were fully engulfed by the ice ball. No serious adverse events occurred related to the IceSense3™ system. At the 1-year follow-up, the FAs were gone in 93 % of the cases. Prior to CA procedure, 76 % of the FAs were palpable. Afterwards in some cases (22 %), a scar/cryo lesion was palpable. 28 % of the patients reported pain, described as mild or moderate, compared to 2 % after 1 year. Cosmetic results at 12 months follow-up were reported as good or excellent in 100 % by physician and in 97 % by patients.ConclusionsThe cryodestruction of the FA using liquid nitrogen system proved functional and safe, while showing meaningful reduction in volume, palpability, pain and cosmetic satisfying outcomes.